Communication through comedy: a drama and theatre project with young people for whom English is a second language. Issue 2 (May 2014) - Shepherd, Lisa
<x xml:space="preserve">Abstract</x> This article explores an eight‐month community theatre project with young people for whom English is a second language. Working as a creative practitioner facilitating young people to explore their personal stories of transition to the UK, the dramatherapist discovered comedy to be an important and poignant vehicle for expression of the emotional and psychological material associated with transition. In this article the author explores her experience of working with a group of young people who came together from all over the world to share their experiences of transition through the use of comedic theatre techniques.